Inside “Pandora’s Box” of Solidarity: Conflicts Between Paid Staff and Volunteers in the Non-profit Sector - López-Cabrera, Rocío; Arenas, Alicia; Medina, Francisco J.; Euwema, Martin; Munduate, Lourdes (Frontiers in Psychology, 2020)
Nonprofit organizations (NPOs), are quite complex in terms of organizational structure, diversity at the workplace, as well as motivational mechanisms and values rationality. Nevertheless, from an Organizational Psychology perspective, the systematic analysis of this context is scarce in the literature, particularly regarding conflicts. This qualitative study analyzes types, prevalence and consequences of conflicts in a large NPO organization considering as theoretical framework several consolidated Organizational Psychology theories: Conflict Theory, Social Comparison Theory and the Equity Theory. Conflicts were analyzed taking into account volunteers’ perspective, who has been consistently protagonist on NPOs research, but also considering paid staff’s perspective, as one of the main stakeholders in these organizations, whose relative power has increase in the past decade due the professionalization of the NPO’s sector. Results confirmed the existence of four types of conflicts: task, process, status and relationship conflicts. Relationship conflict is the least reported type, revealing the protection factor that values and engagement with a social aim have on this organizational context. The most relevant finding is the strong difference between paid staff and volunteers in conflict perceptions, showing paid staff, overall, higher levels of conflicts than volunteers. Findings also show stronger negative consequences for paid staff compared to volunteers. Theoretical and practical implications are discussed.